Baseline morphine consumption may explain between-study heterogeneity in meta-analyses of adjuvant analgesics and improve precision and accuracy of effect estimates - Doleman, Brett; Sutton, Alex J.; Sherwin, Matthew; Lund, Jonathan N.; Williams, John P. (Lippincott, Williams & Wilkins, 2018)
BACKGROUND: Statistical heterogeneity can increase the uncertainty of results and reduce the quality of evidence derived from systematic reviews. At present, it is uncertain what the major factors are that account for heterogeneity in meta-analyses of analgesic adjuncts. Therefore, the aim of this review was to identify whether various covariates could explain statistical heterogeneity and use this to improve accuracy when reporting the efficacy of analgesics.